Prescribing Pattern of Antibiotics among Hospitalized Patients with Urinary Tract Infection - Shrestha, Deepti; Sapkota, Jyotshna; Poudel, Rekha; Shakya Gurung, Rashmi; Aryal, Kiran (Journal of Nepal Health Research Council, 2023)
Background: Urinary tract infection is one of the most common bacterial infections worldwide. It has become one of the most common cause for the hospitalization and sepsis. It is generally treated with antimicrobial agents and fluids. This study was conducted to study the prescribing pattern of antibiotic among hospitalized patients with urinary tract infection. Methods: A descriptive cross-sectional study was conducted in Nepal Medical College Teaching Hospital, Attarkhel, Kathmandu from January 2022 to April 2022. Patients aged 18 years or above of both sex, admitted to various departments with the provisional diagnosis of urinary tract infection prescribed with antibiotics were included in the study. Results: Out of 146 patients admitted with a diagnosis of urinary tract infection, the most commonly prescribed antibiotics during hospital stay were cephalosporin in 102 (69.9%) patients followed by combination of penicillin and beta-lactamase inhibitors (31, 21.2%) and fluoroquinolones (15, 10.3%). Ceftriaxone (78, 53.4%) alone was the most commonly prescribed antibiotic as empirical therapy followed by combination of piperacillin and tazobactam (22, 15.1%). One hundred and forty four (78.6%) patients were prescribed antibiotics from the watch group followed by the access group (21, 11.5 %). E. coli was the most common organism isolated in 29 (76.3%) patients. Conclusions: Cephalosporin was the commonest antibiotic group prescribed in hospitalized patients among which ceftriaxone was commonly prescribed as an empirical therapy. Among AWaRe classification, antibiotics from the watch group were commonly prescribed. Keywords: Antibiotics; ceftriaxone; urinary tract infection